A Review of The Importance of Entrepreneurial Marketing for Small and Medium Enterprises - Padilla Dergal, Jose Guillermo (2012)
The purpose of this paper is to review the impact of entrepreneurial approaches to marketing activities in Small and Medium Enterprises (SMEs). Due to scarce resources and limited market knowledge, scholars suggest that SMEs cannot follow conventional marketing activities. Drawing on earlier research this paper analyses the characteristics and existence of marketing activities that ensure the survival and growth of entrepreneurial ventures. The research was instrumented by using five previous qualitative studies in entrepreneurial and marketing activities. The analysis of the results conclude that successful entrepreneurs undertake unconventional marketing approaches. In addition, the studies provide enough evidence that entrepreneurial marketing is driven by networking and represent an essential tool for SMEs.